МОНГОЛ ДАХЬ СОЦИАЛ ДЕМОКРАТ ҮЗЭЛ СУРТЛЫН ӨНӨӨГИЙН БАЙДАЛ, ЦААШДЫН ХАНДЛАГА - Ц.Ганболд; Ц.БАТБОЛД (Politology, 2023)
In this article, it will consider political party’s pragmatic approach, political ideology, ideal system, value system and political activities system’s briefly meaning and it aims to identify Social Democratic ideology’s present and future direction. In this framework, it explains and specifies the Social Democrat and its ideology and their status in the society and its reason of pragmatic approach and characteristics. It considers the political parties’ responsibility on their activity and cause of their pragmatic approach. It considers briefly and specifies Mongolian Social Democratic and its ideology and present and future situation. Finally, it aims to give an interpretation to the ideology and its future ideology. ТОВЧ ХУРААНГУЙ: Улс төрийн намуудын прагматик хандлага, улс төрийн үзэл суртал, үзэл санааны систем, үнэт зүйлсийн систем, үйл ажиллагааны систем зэргийг тодруулан социал демократ үзэл суртлын өнөө ба ирээдүйн хандлагыг тодруулахыг зорьсон.